Controlling Molecular Doping in Organic Semiconductors - Jacobs, Ian E.; Moulé, Adam J. (Advanced materials (Weinheim), 2017)
The field of organic electronics thrives on the hope of enabling low‐cost, solution‐processed electronic devices with mechanical, optoelectronic, and chemical properties not available from inorganic semiconductors. A key to the success of these aspirations is the ability to controllably dope organic semiconductors with high spatial resolution. Here, recent progress in molecular doping of organic semiconductors is summarized, with an emphasis on solution‐processed p‐type doped polymeric semiconductors. Highlighted topics include how solution‐processing techniques can control the distribution, diffusion, and density of dopants within the organic semiconductor, and, in turn, affect the electronic properties of the material. Research in these areas has recently intensified, thanks to advances in chemical synthesis, improved understanding of charged states in organic materials, and a focus on relating fabrication techniques to morphology. Significant disorder in these systems, along with complex interactions between doping and film morphology, is often responsible for charge trapping and low doping efficiency. However, the strong coupling between doping, solubility, and morphology can be harnessed to control crystallinity, create doping gradients, and pattern polymers. These breakthroughs suggest a role for molecular doping not only in device function but also in fabrication—applications beyond those directly analogous to inorganic doping. Strong interactions between molecular dopants and organic semiconductor morphology are often responsible for charge trapping and low doping efficiency. This study reviews how solution‐processing techniques can control these interactions and render them useful for engineering diffusion rates, doping gradients, and film topography. These breakthroughs suggest new roles for molecular doping in device fabrication as well as function.